Development of a digital twin for data-driven modeling of punch-bending processes using a graphical modeling notation - Peters, Henning; Mazur, Andreas; Pandey, Ankit Kumar; Trächtler, Ansgar; Hammer, Barbara; Homberg, Werner (at - Automatisierungstechnik)
Abstract In punch-bending, products such as brackets, electronic contacts or spring elements are produced from wire-shaped semi-finished products using separation processes and several successive forming processes. Within the multi-stage straightening and bending processes, cross-stage and quantity-dependent effects have a significant influence on the quality of the end product. In order to optimize the punch-bending process with regard to the resulting component deviations and waste rate, this article presents the concept of a digital twin for an innovative hybrid model of a multi-stage punch-bending process. To ensure efficient development and implementation of the digital twin, the graphical modeling notation DSL4DPiFS is used for additional support. It makes it possible to derive the required interfaces of the Asset Administration Shell of the hybrid data-driven model.

DSL4DPiFS – a graphical notation to model data pipeline deployment in forming systems - Vogel-Heuser, Birgit; Zhang, Mingxi; Krüger, Marius; Vicaria, Alejandra; Gardill, Markus; Jiang, Yuyao; Trächtler, Ansgar; Peters, Henning; Liewald, Mathias; Schenek, Adrian; Heinzelmann, Pascal; Weyrich, Michael (at - Automatisierungstechnik)
Abstract Data-driven methods are increasingly utilized in metal forming processes for monitoring and quality optimization. An adapted modeling notation DSL4DPiFS for forming processes is presented to model hardware, software, and data flow aspects to support the design and analysis of data-driven methods. DSL4DPiFS enables metal forming and automation experts to model field-level information as data sources, and the data sinks for data analysis. The notation was adapted to the requirements of selected metal forming processes and evaluated in three case studies.

Modellbasierter Entwurf und Validierung einer Eigenschaftsregelung für das Drückwalzen metastabiler Austenite - Kersting, Lukas; Arian, Bahman; Rozo Vasquez, Julian; Trächtler, Ansgar; Homberg, Werner; Walther, Frank (at - Automatisierungstechnik)
Zusammenfassung Die Eigenschaftsregelung mit einer online-Messung der Bauteileigenschaften ist ein in der Umformtechnik viel diskutiertes, aber kaum validiertes Konzept, um den Automatisierungsgrad bei der Bauteilfertigung weiter zu erhöhen. Dieser Artikel soll helfen, die Lücke beispielhaft für den Fertigungsprozess des Drückwalzens metastabiler Austenite zu schließen. Der metastabile austenitische Edelstahl ändert hierbei während der Verformung seinen α′-Martensitgehalt und damit verbunden die magnetischen Eigenschaften. Deshalb soll über die Regelung das definierte Einstellen des α′-Martensitgehaltes möglich werden. Im Rahmen des vorliegenden Artikels wird gezeigt, wie mittels des modellbasierten Entwurfs die Eigenschaftsregelung ausgelegt und parametriert werden kann. Zudem beinhaltet der Artikel experimentelle Validierungsergebnisse der zuvor entworfenen Eigenschaftsregelung.

Information Circularity Assistance based on extreme data - Gräßler, Iris; Weyrich, Michael; Pottebaum, Jens; Kamm, Simon (at - Automatisierungstechnik)
This paper presents the concept of Information Circularity Assistance, which provides decision support in the early stages of product creation for Circular Economy. Engineers in strategic product planning need to proactively predict the quantity, quality, and timing of secondary materials and returned components. For example, products with high recycled content will only be economically sustainable if the material is actually available in the future product life. Our assumption is that Information Circularity Assistance enables decision makers to incorporate insights from extreme data – high-volume, high-velocity, heterogeneous and distributed data from the product life – into product creation through intelligent Digital Twins. Artificial Intelligence can help to derive sustainable actions in favor of circular products by processing extreme data and enriching it with expert knowledge. The research contributes in three key dimensions. First, a comprehensive literature review is conducted. This review covers concepts of intelligence in Scenario-Technique for strategic product planning, Digital Twin-based analysis of extreme data and relevant technologies from Data Science and Artificial Intelligence. In all areas, the state of the art and emerging trends are identified. Secondly, the study identifies information needs along the steps of the Scenario-Technique and information offerings based on Digital Twins. The concept of Information Circularity Assistance results from the coupling of these demands and offerings, extending the Scenario-Technique beyond traditional expert-based methods. Third, we extend existing Digital Twin methods used in circularity and discuss the deployment of Data Science and Artificial Intelligence algorithms within the product creation process. Our approach uses extreme data to provide a strategic advantage in optimizing product life cycle planning, which is illustrated by two sample applications. The aim is to provide Information Circularity Assistance that will support experienced product planners, developers, and decision makers in the future.
Keywords: Scenario-Technique; Artificial Intelligence; Digital Twin; Large Language Models

Echtzeitfähige Modellierung eines innovativen Drückwalzprozesses für die eigenschaftsgeregelte Bauteilfertigung - Kersting, Lukas; Arian, Bahman; Rozo Vasquez, Julian; Trächtler, Ansgar; Homberg, Werner; Walther, Frank (at - Automatisierungstechnik)
Zusammenfassung Aufgrund aktueller Transformationsprozesse kommt der automatisierten und ressourceneffizienten Fertigung hochfester Leichtbauteile eine steigende Bedeutung zu, beispielsweise im Flugzeug- und Fahrzeugbau. Für kleine Losgrößen bietet sich hier insbesondere das Fertigungsverfahren des Drückwalzens an. Der konventionelle, industriell genutzte Drückwalzprozess stößt allerdings aufgrund der Prozesskomplexität hinsichtlich der Reproduzierbarkeit an seine Grenzen. Dies wird in der Praxis teilweise durch personengebundenes Erfahrungswissen kompensiert. Auch ist es nicht möglich, Bauteileigenschaften definiert einzustellen. Aus diesem Grund bietet der Einsatz einer neuartigen Eigenschaftsregelung Chancen zur Weiterentwicklung des Fertigungsprozesses und die Möglichkeit zur Prozessautomatisierung. Hier werden die Werkzeugbahnen abhängig einer Online-Eigenschaftsmessung über eine zusätzliche Reglerkaskade manipuliert. Die Entwicklung einer solchen Eigenschaftsregelung erfordert den Einsatz geeigneter, modellbasierter Entwurfsmethoden. In diesem Beitrag wird daher ein regelungstechnisches Systemmodell für das Drückwalzen metastabiler austenitischer Edelstähle vorgestellt. Das Simulationsmodell weist aufgrund seiner Echtzeitfähigkeit neben dem Einsatz als reines Entwurfsmodell weitere Nutzungsmöglichkeiten z.B. in Beobachtern auf und grenzt sich somit von domänenspezifischen Simulationstools wie der FEM ab.
Keywords: Electrical and Electronic Engineering; Computer Science Applications; Control and Systems Engineering

An approach to adhesive bond characterisation using guided acoustic waves in multi-layered plates - Zeipert, Henning; Claes, Leander; Johannesmann, Sarah; Lugovtsova, Yevgeniya; Nicolai, Marcel; Prager, Jens; Henning, Bernd (at - Automatisierungstechnik)
An approach for the non-destructive characterisation of adhesive bonds using guided ultrasonic waves is presented. Pulsed laser radiation is used to thermoacoustically excite broadband ultrasonic waves in a multi-layered sample, consisting of a metal plate adhesively joined to a polymeric layer using synthetic resin. The resulting signals are received by a purpose-built piezoelectric transducer. Varying the distance between excitation and detection yields spatio-temporal measurement data, from which the dispersive properties of the propagating waves can be inferred using a two-dimensional Fourier transform, assuming the plates to act as coupled waveguides. Coupled multi-layered waveguides show an effect referred to as mode repulsion , where the distance between certain modes in the frequency-wavenumber domain is assumed to be a measure of coupling strength. Measurements at different stages of curing of the adhesive layer are performed and evaluated. A comparison of the results shows changes in the dispersive properties, namely an increased modal bandwidth for the fully cured sample as well as an increased modal distance.

Verschlüsselte Regelung in der Cloud – Stand der Technik und offene Probleme - Schulze Darup, Moritz (at - Automatisierungstechnik)
Zusammenfassung Zukünftige Regelungskonzepte werden verstärkt auf Cloud-Computing und verteiltes Rechnen setzen. In den resultierenden vernetzten Regelungssystemen werden sensible Daten über öffentliche Netzwerke kommuniziert und auf Plattformen Dritter verarbeitet. Verschlüsselte Regelungen zielen darauf ab, die Vertraulichkeit dieser Daten im gesamten Regelkreis zu sichern. Um dieses Ziel zu erreichen, werden klassische Regelungsalgorithmen so modifiziert, dass sie verschlüsselte Regeleingriffe basierend auf verschlüsselten Systemzuständen berechnen. Zum Einsatz kommen dabei homomorphe Verschlüsselungsverfahren, die einfache mathematische Operationen auf verschlüsselten Daten ermöglichen. Der Artikel erläutert die Implementierung verschlüsselter Regelungen anhand von drei wegweisenden Realisierungen in der Cloud.
Keywords: Electrical and Electronic Engineering; Computer Science Applications; Control and Systems Engineering

Elektromobilität — ein aktuelles Forschungsfeld insbesondere der Regelungstechnik - Kröger, Claus; Böcker, Joachim; Neiß, Konstantin (at - Automatisierungstechnik)
Keywords: Electrical and Electronic Engineering; Computer Science Applications; Control and Systems Engineering

Regelung elektrischer Traktionsantriebe in Elektro- und Hybridfahrzeugen - Böcker, Joachim; Huber, Tobias; Peters, Wilhelm; Pohlenz, Daniel; Specht, Andreas (at - Automatisierungstechnik)